Land Surface Temperature Monitoring with the Help of Remote Sensing - Rahmatzai, Asadullah (Journal of Natural Sciences – Kabul University, 2021)
Temperature plays a major role in climate change, and it is estimated and monitored using various methods. Remote sensing (RS) is the science of collecting and interpreting information about Earth's surface or objects without physical contact. In recent decades, RS has advanced from experimental to operational levels. Thermal RS provides data for geothermal investigations. The role of temperature in climate change can be monitored and estimated through different methods. This research aims to present a technique for Land Surface Temperature (LST) analysis using data from Landsat-8 OLI/TIR to retrieve the LST of Kabul city on February 13, 2015. The results show a mean LST of 13.22°C, which matches the ground data. This article provides valuable information for researchers and students to apply the method for estimating LST in their research areas.